Unveiling microbial succession dynamics on different plastic surfaces using WGCNA. - Keren Davidov; Sheli Itzahri; Liat Anabel Sinberger; Matan Oren (PLoS ONE)
Over recent decades, marine microorganisms have increasingly adapted to plastic debris, forming distinct plastic-attached microbial communities. Despite this, the colonization and succession processes on plastic surfaces in marine environments remain poorly understood. To address this knowledge gap, we conducted a microbiome succession experiment using four common plastic polymers (PE, PP, PS, and PET), as well as glass and wood, in a temperature-controlled seawater system over a 2- to 90-day period. We employed long-read 16S rRNA metabarcoding to profile the prokaryotic microbiome's taxonomic composition at five time points throughout the experiment. By applying Weighted Gene Co-expression Network Analysis (WGCNA) to our 16S metabarcoding data, we identified unique succession signatures for 77 bacterial genera and observed polymer-specific enrichment in 39 genera. Our findings also revealed that the most significant variations in microbiome composition across surfaces occurred during the initial succession stages, with potential intra-genus relationships that are linked to surface preferences. This research advances our understanding of microbial succession dynamics on marine plastic debris and introduces a robust statistical approach for identifying succession signatures of specific bacterial taxa.